Caged-electron states in endohedral Li fullerenes - Yang, Yi-Fan; Gromov, Evgeniy; Cederbaum, Lorenz S. (The journal of physical chemistry letters, 2019)
ABSTRACT: By employing large-scale high-level EA-EOM-CCSD calculations, we have computed and analyzed the low-lying states of neutral LiC60. Apart from one state, all statesare found to be charge-separated states of the type Li+@C60−.The new state is thefirst reported non-charge-separated statein endohedral alkali fullerenes. This caged-electron state isanalyzed in detail. Arguments are given that in larger highlysymmetric endohedral fullerenes the caged-electron state canbe the electronic ground state of the system. HF and DFTcalculations on Li@C180indeedfind that the caged-electronstate is the ground state and that in its equilibrium geometryLi sits at the center of the cage. Applications are mentioned.
Gesehen am 11.02.2020
Gesehen am 11.02.2020